2020
DOI: 10.1002/hed.26186
|View full text |Cite
|
Sign up to set email alerts
|

Use of narrowband imaging for the diagnosis and screening of laryngeal cancer: A systematic review and meta‐analysis

Abstract: We evaluated the diagnostic accuracy of narrowband imaging (NBI) in terms of detecting laryngeal cancer compared to that of white light endoscopy (WLE). Two reviewers individually searched the six databases for studies published between the first record date and December 31, 2019. We recorded the numbers of true positives, true negatives, false positives, and false negatives. Quality Assessment of Diagnostic Accuracy Studies ver. 2 software was used to assess the studies. The extent of the inter‐rater agreemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 45 publications
(62 reference statements)
0
13
0
3
Order By: Relevance
“…The increases in number of incident cases during 2007-2017 might be due to population growth and aging. The improvements in disease managements, ear-lier diagnosis and better adoption of integrated therapeutic schemes, the popularity of fiber-optic laryngoscope, Computed Tomography (CT), and Magnetic Resonance Imaging(MRI) examinations contributed to the declined percentage decreases in age-standardized DALY and death rates in our study [7].…”
Section: Discussionmentioning
confidence: 81%
“…The increases in number of incident cases during 2007-2017 might be due to population growth and aging. The improvements in disease managements, ear-lier diagnosis and better adoption of integrated therapeutic schemes, the popularity of fiber-optic laryngoscope, Computed Tomography (CT), and Magnetic Resonance Imaging(MRI) examinations contributed to the declined percentage decreases in age-standardized DALY and death rates in our study [7].…”
Section: Discussionmentioning
confidence: 81%
“…A value of 1 indicated that the presence or absence of disease could not be inferred. The logarithm of each DOR was calculated to obtain an approximately normal distribution [ 42 ]. The SROC approach is the method of choice for the meta-analysis of studies reporting both sensitivity and specificity.…”
Section: Methodsmentioning
confidence: 99%
“…Durch den Einsatz von Narrow Band Imaging (NBI) ist es mittels Verwendung schmalbandiger optischer Filter gelungen, eine verbesserte Gefäßdarstellung in Übersichtsaufnahmen der Stimmlippen zu erreichen [ 9 , 21 ]. Die Überlegenheit von NBI gegenüber der Weißlichtendoskopie (WLE) bei der Unterscheidung zwischen benignen und malignen Veränderungen und deren Vorstufen wurde in mehreren Studien und Metaanalysen belegt [ 13 , 26 ]. Die Rolle eines weiteren Verfahrens, der Kontaktendoskopie (KE), wurde schon in den 1990er-Jahren u. a. für die genaue Betrachtung vaskulärer Veränderungen der Stimmlippen hervorgehoben [ 1 ].…”
Section: Kontaktendoskopie Mit Narrow Band Imagingunclassified
“…Bei der WLE ist die genaue Betrachtung und Analyse solcher Gefäßmuster nur eingeschränkt möglich. Die Endoskopie mit NBI hat neue Möglichkeiten in diesem Gebiet eröffnet [ 13 , 19 ]. NBI ist ein optisches Filtersystem, das über die Reduzierung des Lichts auf 2 spektrale Regionen im blauen und grünen Anregungsbereich (400–430 nm und 525–555 nm) zu einer deutlich stärker kontrastierten Darstellung oberflächlich gelegener Gefäße führt.…”
Section: Diskussionunclassified
See 1 more Smart Citation